Threshold concepts in group-based mentoring and implications for faculty development: A qualitative analysis. (3rd August 2021) - Kvernenes, Monika; Valestrand, Eivind Alexander; Schei, Edvin; Boudreau, J. Donald; Ofstad, Eirik Hugaas; Hokstad, Leif Martin
Abstract: Introduction: The literature on faculty development programs for mentors is scarce. This study examines mentors' experiences and challenges, with the aim of identifying threshold concepts in mentoring. It also discusses the implications for the faculty development of mentors. Methods: Semi-structured interviews solicited personal narratives and reflections on mentors' lived experiences. Data analysis was guided by the threshold concepts framework allowing for the identification of significant and transformative shifts in perspectives. Results: We interviewed 22 mentors from two Norwegian and one Canadian medical school with group-based mentoring programs. The mentoring experience involved four significant threshold concepts: focusing on students' needs; the importance of creating a trusting learning space; seeing oneself through the eyes of students; and aligning mentor and physician identities. Conclusion: Taking on a mentor role can provoke personal and professional dilemmas while also sparking growth. The trajectories of developing as a mentor and as a professional physician may be seen to mutually validate, mirror and reinforce each other. Faculty development programs designed specifically for mentors should aim to stimulate reflection on previous learning experiences and strive for a successful alignment of the distinct pedagogical and clinical content knowledge required to fulfill various professional roles.